2003
DOI: 10.1055/s-0040-1715736
|View full text |Cite
|
Sign up to set email alerts
|

Communication in Noise with Acoustic and Electronic Hearing Protection Devices

Abstract: The purpose of the present study was to evaluate communication ability in noise at two signal presentation levels when using acoustic and electronic hearing protection devices (HPDs). Fourteen normal hearing subjects were fitted binaurally with custom acoustic HPDs (ER-15) and custom electronic HPDs (Starkey SA T9). Probe microphone measurements were obtained on 28 ears for three experimental conditions (open ear, acoustic HPD, electronic HPD) at four input signal levels (60, 70, 80, 90 dB SPL). Also, communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The summarized results of the reviewed studies according to the PICOS criteria are displayed in Table 3 . The participants included individuals with both normal hearing [ 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and hearing loss [ 3 , 5 , 26 ]. Specifically, Smalt et al reported on one single individual with a threshold of 30 dB HL in one ear [ 3 ] and Abel et al had 24 older adults with hearing loss [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…The summarized results of the reviewed studies according to the PICOS criteria are displayed in Table 3 . The participants included individuals with both normal hearing [ 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and hearing loss [ 3 , 5 , 26 ]. Specifically, Smalt et al reported on one single individual with a threshold of 30 dB HL in one ear [ 3 ] and Abel et al had 24 older adults with hearing loss [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although passive noise reduction HPDs which have a low noise reduction rating (NRR) showed increased speech intelligibility in the presence of background noise [11], active noise reduction HPDs provided substantial bene ts for speech recognition performance, especially for the hearingimpaired users [28]. Plyler and Klumpp also suggested that active noise reduction HPDs may be bene cial for individuals with sensorineural hearing loss [21]. Further considering the characteristics and requirements of users who would be recommended and/or mandated for HPDs, Manning et al reported on the bene ts of bone-conduction HPDs for tinnitus patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…The summarized results of the reviewed studies according to the PICOS criteria are displayed in Table 3. The participants included individuals with both normal hearing [4,[6][7][8][9][10][11][12][20][21][22][23][24][25][26][27] and hearing loss [3,5,28]. Speci cally, Smalt et al reported on one single individual with a threshold of 30 dB HL in one ear [3] and Abel et al had 24 older adults with hearing loss [5].…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations